Nanotechnological approaches against Chagas disease - Romero, Eder Lilia (2010)
Over several thousand years, the flagellated Trypanosome cruzi?causative agent of Chagas disease developed a complex life cycle between the reduviidae vectors and its human hosts. Due to their silent and hidden location, the intracellular amastigotes are mainly responsible for the nearly 50,000 annual deaths caused by the chronic chagasic cardiomyopathy. Chagas disease is the most important parasitic disease in the Americas country-region, though treatments have not evolved towards a more efficient pharmacotherapy that (i) eradicates the scarce amastigotes present at the indeterminate/chronic form and (ii) employs less toxic drugs than benznidazole or nifurtimox. Nano-drug delivery systems (nanoDDS) represent useful means to selectively deliver the drug to intracellular targets. However, preclinical research in Chagas must be extended in order to improve the chances of a clinical implementation. The stages involved in this process are (i) selection of the appropriate drug for a specific parasite, (ii) development of a drug-loaded nanoDDS structure that displays the adequate pharmacokinetics, biodistribution and intracellular transit and (iii) selection of the right parasite form to target and the right stage of the disease for the treatment to be started. In this review we will critically overview the few research works published in the last 20 years in the context of nanotechnology and Chagas diseases and highlight the gaps in knowledge towards the design of more efficient medicines to address this endemic.